Pengembangan E-LKPD Berbasis Problem Solving Untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik Pada Materi Hidrolisis Garam - Celyta Nirmala Putri Talia; Harun Nasrudin (PendIPA Journal of Science Education, 2026)
This study aims to develop a feasible problem-solving-based E-LKPD on salt hydrolysis material to improve students’ critical thinking skills. The indicators of critical thinking skills include interpretation, analysis, evaluation, and inference. The research employed a Research and Development (R&D) method using the 4D model. The research procedures consisted of the define, design, and were limited to the develop stage. The feasibility of the E-LKPD was reviewed based on validity, practicality, and effectiveness aspects. The validity of the E-LKPD, based on content and construct aspects, obtained a mode score of 5, categorized as valid. The practicality of the E-LKPD was reviewed from the response questionnaire, which obtained an average percentage of 97% categorized as very strong, and the observation results of students’ activities showed an average percentage of relevant activities of 97%, categorized as very strong, while irrelevant activities obtained 3%, categorized as very weak. The effectiveness of the E-LKPD was reviewed from the N-Gain Score results of the pretest and posttest on critical thinking skills, with an average score of 0.81 categorized as high, and the Paired Sample T-Test showed a significance value of ≤ 0.05, indicating that H1 was accepted. These results indicate that the implementation of the problem-solving-based E-LKPD is effective in improving students’ critical thinking skill.